THE STEREOTYPES OF THE MAIN CHARACTER IN AMANDA BROWN’S LEGALLY BLONDE NOVEL - Rina - Lestari (Universitas Nasional, 2021)
AbstractBecause of the improvement in every part of human life, the novel has become a famous literary work that can reflect the condition of society. The research entitled